Brussels and Washington: two federal capital cities with two similar metropolitan experiences? - Caroline Van Wynsberghe (Brussels Studies, 2013)
This article follows a comparative study mission. It shows that the metropolitan development of Brussels is clearly atypical when compared to the literature or the example of Washington, DC. It falls within the scope of Belgian mechanisms of compromise rather than the implementation of classic models of metropolitan cooperation, which often emphasise the voluntary involvement of the different stakeholders. In the case of Brussels, the metropolitan reality was imposed “from above”, even if it was claimed by some of the partners of the state reform. Contrary to Washington, there are no incentives planned by the federal authorities. The Brussels metropolitan community is also unique because this structure is not applicable to other big cities in the country, whereas the metropolitan organisation in Washington simply applies a rule which is common to all major American cities. The comparison also underlines the time required for cooperation to take root. Metropolitan cooperation has been practised in Washington for more than sixty years and has developed gradually, starting with the most straightforward issues such as public transport.